Validated RP-HPLC Method for the Assay of Etoricoxib (A Non-Steroidal Anti-Inflammatory Drug) in Pharmaceutical Dosage Forms - Srinivasu Topalli; T. G. Chandrashekhar; M. Mathrusri Annapurna (E-Journal of Chemistry)
A simple, accurate, sensitive and reproducible reverse phase high performance liquid chromatographic method has been developed for the quantitative determination of Etoricoxib in pharmaceutical dosage forms. The assay was performed on Hypersil ODS C-18 (250 x 4.6 mm., 5µm particle size) column using acetonitrile and potassium dihydrogen phosphate buffer (pH 4.2) (46:54 % v/v) as mobile phase with UV detection at 280 nm (flow rate 1.2 ml/min). Bromhexine was used as an internal standard. Quantization was achieved by measurement of the peak area ratio of the drug to the internal standard. The limit of detection (LOD) and the limit of quantification (LOQ) were 0.0704 µg ml-1 and 0.2134 µg ml-1 respectively. Each analysis required no longer than 10 minutes. The calibration curve was linear over the concentration range from 0.5-85.0 µg ml-1. The retention times of Etoricoxib and Bromhexine were found to be 3.083 and 7.631 minutes respectively. The proposed method was validated according to the ICH guidelines and can be used successfully to analyse marketed formulations.